A novel electrochemical immunosensor based on biomaterials for detecting carcinoembryonic antigen biomarker in serum samples - Sajedeh Sobhanparast; Payam Shahbazi-Derakhshi; Jafar Soleymani; Amir Amiri-Sadeghan; Alireza Herischi; Nader Chaparzadeh; Younes Aftabi (Scientific Reports)
Abstract A new label-free electrochemical immunosensor was developed to detect carcinoembryonic antigen (CEA), a key diagnostic biomarker for various cancers. The surface of a glassy carbon electrode (GCE) was modified using a layer-by-layer assembly method incorporating sodium alginate (SA), gold nanoparticles (AuNPs), and gamma-manganese dioxide/chitosan (γ.MnO₂-CS). This modification enhanced the functional surface area and electrode conductivity, thereby improving the electrochemical response and sensitivity for CEA detection. Methods including cyclic voltammetry (CV) and differential pulse voltammetry (DPV) were used to evaluate the immunosensor`s performance.The sensor quantified CEA concentrations in serum samples by monitoring current variations at the oxidation peak, resulting from the formation of CEA antibody–CEA antigen complexes on the electrode surface. The sensor exhibited a linear response to CEA concentrations ranging from 10 fg/mL to 0.1 µg/mL, with a limit of detection (LOD) of 9.57 fg/mL and a limit of quantification (LOQ) of 31.6 fg/mL. The morphology and structural properties of the synthesized γ.MnO₂-CS nanocomposite and the modified electrode surface were characterized utilizing field-emission scanning electron microscopy (FE-SEM), Brunauer–Emmett–Teller (BET) and Barrett-Joyner-Halenda (BJH), X-ray diffraction (XRD), energy-dispersive X-ray spectroscopy (EDX), atomic force microscopy (AFM), dynamic light scattering (DLS), zeta potential analysis, and Fourier transform infrared (FTIR) spectroscopy. The results highlight the potential clinical applicability of this electrochemical immunosensor for detecting CEA levels in human serum samples.